2012
DOI: 10.1111/odi.12039
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between salivary mucin or amylase and the periodontal status

Abstract: The increment of mucin and amylase output in relation to periodontal status indicates that salivary glands respond to the disease by increasing the protective potential of saliva when necessary and return to the normal rate of secretion after the resolution of the inflammatory process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1
5

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 27 publications
7
30
1
5
Order By: Relevance
“…In support of this idea, CXCL8 staining was increased in the epithelium of patients with cystic fibrosis and colocalized with mucins [25]. Mucins are correlated with the severity of periodontal disease [26]. However, mucin 2 can even be inversely correlated with CXCL8 expression, at least in pediatric patients with Crohn's disease [27].…”
Section: Discussionsupporting
confidence: 54%
“…In support of this idea, CXCL8 staining was increased in the epithelium of patients with cystic fibrosis and colocalized with mucins [25]. Mucins are correlated with the severity of periodontal disease [26]. However, mucin 2 can even be inversely correlated with CXCL8 expression, at least in pediatric patients with Crohn's disease [27].…”
Section: Discussionsupporting
confidence: 54%
“…The increased protein levels in our study in the test groups could be due to the inflammatory process that activates the sympathetic system to enhance the synthesis and secretion of some proteins (as evidenced by increased amylase levels) thereby increasing the protective potential of saliva against the diseases [12,13].…”
Section: Collection Of Salivamentioning
confidence: 99%
“…The increased levels may be due to the response of salivary glands to inflammatory diseases like gingivitis and periodontitis resulting in increased synthesis and secretion of certain acinar proteins like α-amylase so as to enhance the oral defense mechanism [12,13].…”
Section: Collection Of Salivamentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that HIF-1 mediated the induction of TFF gene expression and provided an adaptive link for the maintenance of the barrier function during hypoxia of gastric/intestinal lining cells [84,85]. Salivary mucins form a protective layer on the oral surfaces including that of oral sulcular and junctional epithelia, which serve as a physical barrier against bacterial invasion and function as essential antimicrobial macromolecules [86,87]. Similar to TFF, mucins' production was upregulated in hypoxia [88].…”
Section: Hif and Epithelial Barrier Functionmentioning
confidence: 99%